2005
DOI: 10.1101/sqb.2005.70.041
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Telomerase by Human Papillomaviruses

Abstract: Nearly 20% of cancers worldwide have a component of their etiology that is due to infectious agents. In some cases, infection has an indirect effect, such as the immunosuppression caused by HIV or the inflammation caused by Helicobacter pylori, but in other cases, such as human papillomaviruses (HPVs), viral gene products persist in the cancer and directly promote neoplasia. Understanding the mechanisms by which the viral genes disrupt the checkpoints that normally protect cells from cancer will likely provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Mechanistically, it is thought that phosphorylation regulates E6 binding to PDZ‐domain proteins and creates an alternative binding‐site, which allows E6 to associate with members of the cellular 14‐3‐3 protein family . The high‐risk E6 proteins are also characterized by an ability to upregulate telomerase activity and to maintain telomere integrity during repeated cell divisions, as well as by their ability to mediate p53 degradation within the cell. Both high‐risk and low‐risk E6 proteins inactivate p53 function, which suggests an important role in the virus life cycle, but only high‐risk types stimulate its ubiquitination and proteosome‐dependent degradation (see section on cancer progression below) .…”
Section: Papillomavirus Life Cycle Organization In the Infected Epithmentioning
confidence: 99%
“…Mechanistically, it is thought that phosphorylation regulates E6 binding to PDZ‐domain proteins and creates an alternative binding‐site, which allows E6 to associate with members of the cellular 14‐3‐3 protein family . The high‐risk E6 proteins are also characterized by an ability to upregulate telomerase activity and to maintain telomere integrity during repeated cell divisions, as well as by their ability to mediate p53 degradation within the cell. Both high‐risk and low‐risk E6 proteins inactivate p53 function, which suggests an important role in the virus life cycle, but only high‐risk types stimulate its ubiquitination and proteosome‐dependent degradation (see section on cancer progression below) .…”
Section: Papillomavirus Life Cycle Organization In the Infected Epithmentioning
confidence: 99%
“…This action blocks the anti proliferative and pro apoptotic activities of p53 in response to DNA damage and cellular stress caused by aberrant S-phase entry [69]. HR HPV E6 expression also upregulates telomerase activity, allowing the maintenance of telomere integrity despite repeated cell divisions [7072]. Additionally, HR HPV E6 proteins target cellular PDZ domain containing proteins that regulate cell contact and signaling pathways [73, 74].…”
Section: 5 Hpv Productive Infection and Lifecyclementioning
confidence: 99%
“…We and others have shown that E6 appears to activate hTERT transcription through Myc binding sites in the hTERT promoter (Gewin and Galloway, 2001;Oh, Kyo, and Laimins, 2001;Veldman et al, 2001). However, E6 does not induce Myc expression (Galloway et al, 2005;Gewin and Galloway, 2001;Oh, Kyo, and Laimins, 2001;Veldman et al, 2001) nor increase Myc binding to the hTERT promoter (Galloway et al, 2005;Sekaric, Cherry, and Androphy, 2008;Veldman et al, 2003); Myc protein binds to the promoter in the presence or absence of E6 protein in keratinocytes (Galloway et al, 2005;Sekaric, Cherry, and Androphy, 2008;Veldman et al, 2003). Interestingly, E6 associates with Myc in vivo and in vitro and both bind to the core hTERT promoter (Veldman et al, 2003).…”
Section: Introductionmentioning
confidence: 97%